THE INFLUENCE OF SELF-SERVICE TECHNOLOGY AND CUSTOMER RELATIONSHIP MARKETING ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION - Girsang, Runita Kartika Sari; Sumiati, Sumiati; Djawahir, Achmad Helmy (Universitas Brawijaya, Indonesia, 2021)
The purpose of this study is to explain the effect of self-service technology and customer relationship marketing on customer loyalty mediated by customer satisfaction. This research is quantitative research with an explanatory research approach. This research was conducted on customers who have an account at PT. Bank Central Asia, Tbk Tulungagung Branch, a minimum of three years is 82 respondents. Data collection uses questionnaires, documentation, and interviews with SmartPLS version 3.0 analysis tools. The result of the research shows that the direct influence of self-service technology influence on customer satisfaction and the influence of self-service technology on customer loyalty has a significant influence. The influence of customer relationship marketing on customer satisfaction and the influence of customer relationship marketing on customer loyalty has a significant influence. And, the effect of customer satisfaction on customer loyalty has a significant influence. The results of research for indirect influence, namely the influence of self-service technology on customer loyalty through customer satisfaction and influence customer relationship marketing to customer loyalty through customer satisfaction has mediation relationship. The next researcher needs to re-analyze self-service technology, customer relationship marketing as a variable that can increase customer loyalty in other companies that show different characteristics of the subjects of this study. Besides, it needs to be done on government bank customers who have certain characteristics, so that research can be generalized, namely to private companies or government companies.